AN IMPROVED SYNTHESIS OF P-PHENYLENE-BRIDGED METHYLATED BINUCLEAR FERROCENE - Yuvaraja Dibdalli; Cristian Valdebenito; Mungalimane Amshumali; Elies Molins; Cesar Morales (Journal of the Chilean Chemical Society, 2022)
This contribution describes an updated synthetic route along with full characterization of [{CpFe}2-p-Ph’] with p-Ph’: p-Bis{2,3,4,5-tetramethylcyclopentadienyl}benzene). The complex reported here was characterized by 1H and 13C NMR, elemental analysis, the X-ray crystal structure, and Mössbauer spectroscopy. From the crystallographic analysis, it was found that both CpFe fragments are coordinated to opposite sites of the p-Ph’ ligand. In addition, the analysis through of 1H and 13C NMR spectroscopy, confirm that the synthesis and yield of just one isomer of this compound.